MAARTENS, J. Inventory of documents - MAARTENS, J. (ARCA, 2018)
Two scrap books regarding Dr H.F. Verwoerd; Adv. B.J. Vorster
COVERAGE: 0.10 metres
Keywords: MAARTENS, J.; Inventories; Politicians; National Party; Dr HF Verwoerd; Adv. BJ Vorster